2018
DOI: 10.1016/j.omtn.2018.08.016
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA199a-Based Post-transcriptional Detargeting of Gene Vectors for Hepatocellular Carcinoma

Abstract: A gene therapeutic platform needs to be both efficient and safe. The criterion of safety is particularly important for diseases like hepatocellular carcinoma (HCC), which develop in a background of an already compromised liver. Gene vectors can be constructed either by targeting HCC or by detargeting liver and/or other major organs. miRNA-based negative detargeting has gained considerable attention in recent times due to its effectiveness and the ease with which it can be adapted into current gene delivery vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Additionally, the field of AAV vectorology has now advanced to a stage where the capsid can be tailored to transduce specific cell types [9,10]. Capsid engineering combined with AAV genome modification using cell type-specific gene regulatory elements like enhancers/promoters for transcriptional targeting [11] and cell/tissue-specific miRNAs for post-transcriptional targeting [12,13] provides diverse tools to reduce off-target effects [14].…”
mentioning
confidence: 99%
“…Additionally, the field of AAV vectorology has now advanced to a stage where the capsid can be tailored to transduce specific cell types [9,10]. Capsid engineering combined with AAV genome modification using cell type-specific gene regulatory elements like enhancers/promoters for transcriptional targeting [11] and cell/tissue-specific miRNAs for post-transcriptional targeting [12,13] provides diverse tools to reduce off-target effects [14].…”
mentioning
confidence: 99%
“…miRNA-mediated regulation of transgene expression by engineering miR-BSs in rAAV expression cassettes has proven to reduce transgene-specific immune responses. Binding sites against miR-122, miR-199, miR-1, miR-183, and miR-206 can successfully detarget transgene expression from tissues like liver, heart, dorsal root ganglia and skeletal muscles (35,36,(95)(96)(97)(98). We previously demonstrated that miR-142BS elements can blunt CTL activation and can confer sustained transgene expression in transduced mouse TA muscle (42).…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA‐based therapeutic strategies may alter the expression networks of HCC, thereby significantly affecting cell behavior and making it possible to cure HCC. Virus‐based delivery system or non‐viral systems including nanoparticles, lipid‐based vesicles, exosomes, and liposomes can deliver miRNAs 112–115 . Delivery of miR‐26a using an exosomes‐based nanosystem inhibited proliferation of HCC 113 .…”
Section: Mirnas In the Treatment Of Hccmentioning
confidence: 99%
“…Virus-based delivery system or non-viral systems including nanoparticles, lipid-based vesicles, exosomes, and liposomes can deliver miRNAs. [112][113][114][115] Delivery of miR-26a using an exosomes-based nanosystem inhibited proliferation of HCC. 113 Targeted delivery of miR-199a-3p using self-assembled dipeptide nanoparticles or exosomes reduced HCC efficiently.…”
Section: Mirna S In the D Iag Nos Is Of H Ccmentioning
confidence: 99%